Clustering composition, composite cat litter and preparation method and application of composite cat litter

By adding specific pregelatinized starch, polyacrylamide and sodium-based bentonite to the desert sand, a cat litter composition with high clump strength and rapid water absorption was prepared, which solved the problems of low clump strength and high clumping of existing cat litters, and achieved better usage effects.

CN119790997APending Publication Date: 2025-04-11广州喂来宠物科技有限公司

Patent Information

Application Number
CN202411940009.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When existing cat litter uses desert sand as the main material, the cluster strength is low and easy to disperse, and it is easy to stick to the bottom after absorption, which increases the difficulty of processing.

Method used

Aggregation composition with good clump strength and water absorption rate is prepared by adding pregelatinized starch with a specific gelatinization degree and amylopectin mass content to the desert sand.

Benefits of technology

It significantly improves the strength of cat litter, reduces the occurrence of sticky bottom phenomenon, and has excellent water absorption speed, can quickly form clumps, meeting the daily cleaning needs of pet excrement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790997A_ABST
    Figure CN119790997A_ABST
Patent Text Reader

Abstract

The invention discloses a caking composition, composite cat litter as well as a preparation method and application of the composite cat litter. The caking composition is prepared from the following components in parts by weight: 74 to 76 parts of desert sand, 18 to 22 parts of sodium bentonite, 2 to 3 parts of pregelatinized starch, 1 to 3 parts of polyacrylamide and 0.5 to 1.5 parts of solvent; the gelatinization degree of the pregelatinized starch is 73-86%, and the mass content of amylopectin in the pregelatinized starch is 75-84%; the molecular weight of the polyacrylamide is 1400 million to 20 million. The caking composition provided by the invention has relatively good caking strength, is less prone to a bottom sticking phenomenon, has excellent water absorption speed, and can rapidly agglomerate. The use of bean fiber and starch is reduced, and the consumption of non-renewable resources such as bentonite ore is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of pet products, and more specifically, relates to a clumping composition, a composite cat litter, and a preparation method and application thereof. Background Art

[0002] As a pet product, cat litter is currently mainly plant cat litter and bentonite cat litter. Plant cat litter needs to be added with edible raw materials such as pea fiber, corn starch or cassava starch; while bentonite used in bentonite cat litter is a non-renewable resource. Humans continue to exploit and utilize it, which has led to a decrease in the reserves of mineral soil and a certain impact on the environment. As people's pursuit of the quality of living environment continues to improve, environmental protection issues have received increasing attention. It is particularly important to develop a cat litter that can both meet the needs of cats and reduce damage to the environment.

[0003] Desert sand, also known as mobile sand or flying sand, is a kind of sand that is prevalent in desert areas. Its particles are relatively fine and usually yellow or brown. Using desert sand to replace plant sand and bentonite as the main material for absorbing cat excrement is a more environmentally friendly choice, and desert sand itself has a certain water absorption rate and agglomeration effect, but the cohesiveness of desert sand itself is poor, and the prepared cat litter has low agglomeration strength. When stepped on by a cat or a shovel is touched, the agglomeration is easy to disperse, which increases the difficulty of processing. In addition, after the existing cat litter absorbs cat excrement, due to the large thickness of the agglomeration or the large gram weight of the agglomeration, the sticky bottom phenomenon (i.e., the cat litter absorbing cat excrement adheres to the wall or bottom of the cat litter basin) often occurs, further increasing the difficulty of processing cat litter. Therefore, how to develop a kind of cat litter with good agglomeration strength based on desert sand and reduce the sticky bottom phenomenon of cat litter has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the above-mentioned existing technical problems, the primary purpose of the present invention is to provide a clumping composition, which has good clumping strength, is less likely to stick to the bottom, has excellent water absorption speed, and can quickly clumping.

[0005] The second object of the present invention is to provide a method for preparing the agglomeration composition.

[0006] A third object of the present invention is to provide an application of a clumping composition in preparing cat litter.

[0007] A fourth object of the present invention is to provide a composite cat litter.

[0008] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0009] The present invention claims protection for a clumping composition, which comprises, by weight: 74-76 parts of desert sand, 18-22 parts of sodium bentonite, 2-3 parts of pregelatinized starch, 1-3 parts of polyacrylamide, and 0.5-1.5 parts of solvent;

[0010] The gelatinization degree of the pregelatinized starch is 73-86%, the mass content of amylopectin in the pregelatinized starch is 75-84%; and the molecular weight of the polyacrylamide is 14 million to 20 million.

[0011] The present invention provides a clumping composition based on desert sand. The inventors have found through research that pregelatinized starch with a specific gelatinization degree and amylopectin mass content can not only produce strong viscosity when it meets water in a desert sand system, but also significantly improve the clumping strength of the composition system, making it difficult to disintegrate after absorbing liquid; and can also effectively reduce the thickness and gram weight of the clumping, and improve the water absorption speed.

[0012] Furthermore, the water absorption rate of desert sand itself is not high, but polyacrylamide with a specific molecular weight can make desert sand have excellent bonding properties and a good water absorption rate, and can significantly reduce the agglomeration thickness of the desert sand system, making the agglomerated material less likely to stick to the bottom.

[0013] Furthermore, the inventors found through research that sodium bentonite is a material with good water absorption and agglomeration properties. Pregelatinized starch, polyacrylamide and desert sand are difficult to form a stable large particle. Directly adding them to desert sand will result in uneven mixing. The addition of sodium bentonite can improve the mixing state of desert sand and other components in the system, achieving a better mixing state, thereby improving the water absorption and agglomeration properties of the composition. The present invention overcomes the technical difficulty of mixing powdered raw materials with large particle raw materials, and develops a agglomeration composition suitable for preparing cat litter, meeting consumers' daily cleaning needs for pet excrement.

[0014] The present invention uses desert sand as the main material, adopts pregelatinized starch with a specific gelatinization degree and amylopectin mass content, adopts polyacrylamide with a specific molecular weight, and is matched with sodium bentonite. The prepared agglomeration composition has good agglomeration strength, is less likely to stick to the bottom, and has less loss of the agglomeration composition; and has an excellent water absorption speed and can quickly form agglomerates.

[0015] The agglomerating composition provided by the present invention can be used as cat litter, aiming to provide a more environmentally friendly and economical cat litter for pets, which is beneficial to reducing the use of bean fiber and starch, reducing the consumption of non-renewable resources such as bentonite ore, and turning sand in the desert into treasure through post-processing technology, which has a positive effect on the control of environmental desertification.

[0016] Specifically, the degree of gelatinization of the pregelatinized starch can be 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, etc., or an interval range formed by any of the above values, such as 73-78%, 80-83%, etc., but the present invention is not limited thereto.

[0017] Specifically, the mass content of the amylopectin can be 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, etc., or an interval range formed by any of the above values, such as 75-79%, 78-84%, etc., but the present invention is not limited thereto.

[0018] Specifically, the molecular weight of the polyacrylamide can be 14 million, 16 million, 18 million, 20 million, etc., or an interval range formed by any of the above values, such as 14 million-16 million, 16 million-18 million, etc., but the present invention is not limited thereto.

[0019] Preferably, in the sodium bentonite, the colloid value is 350ml-620ml / 15g. Specifically, in the sodium bentonite, the colloid value is 351.7-605.6ml / 15g. Under this preferred condition, the agglomerates of the agglomeration composition after agglomeration have lower agglomeration thickness and agglomeration gram weight, and are less likely to stick to the bottom; in addition, it also has higher agglomeration strength and better water absorption speed. Specifically, the colloid value can be 350ml / 15g, 400ml / 15g, 450ml / 15g, 500ml / 15g, 550ml / 15g, 600ml / 15g, etc., or the interval range formed by any of the above values, such as 400-450ml / 15g, 500-600ml / 15g, etc., and the present invention is not limited thereto.

[0020] Preferably, the solvent is selected from water, or a mixed solution of an alcohol solvent and water. More specifically, the alcohol solvent includes but is not limited to ethanol and the like.

[0021] Specifically, based on weight parts, it includes: 74-76 parts of desert sand, 18-20 parts of sodium bentonite, 2.5-2.8 parts of pregelatinized starch, 2-2.8 parts of polyacrylamide, and 0.5-0.8 parts of solvent.

[0022] Specifically, the gelatinization degree of the pregelatinized starch is 73.2-85.3%, and the mass content of amylopectin in the pregelatinized starch is 78.8-82.8%.

[0023] Specifically, the agglomerated composition has a diameter of 0.5-4 mm.

[0024] Specifically, the moisture content of the agglomeration composition is ≤8%. Further preferably, the moisture content of the agglomeration composition is 5-8%.

[0025] Furthermore, the present invention claims protection for a method for preparing the above-mentioned agglomeration composition, comprising the following steps: mixing sodium bentonite, pregelatinized starch, polyacrylamide and a solvent, granulating, drying, and then mixing with desert sand to prepare the agglomeration composition.

[0026] Furthermore, the present invention seeks to protect the use of the water-absorbing and agglomerated composition in the preparation of cat litter.

[0027] Furthermore, the present invention claims protection for a composite cat litter comprising the above-mentioned agglomerating composition.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention provides a clumping composition and its application in composite cat litter. The clumping composition is prepared by using desert sand as a base material and adding pregelatinized starch with a specific gelatinization degree and amylopectin mass content, polyacrylamide with a specific molecular weight, and sodium bentonite to the desert sand. The clumping composition has good clumping strength, is less likely to stick to the bottom, and has an excellent water absorption speed, can quickly form clumps, and meets consumers' daily cleaning needs for pet excrement.

[0030] (2) The present invention provides a more environmentally friendly and economical cat litter, which is beneficial to reducing the use of bean fiber and starch, reducing the consumption of non-renewable resources such as bentonite in cat litter, turning sand in the desert into treasure, and playing a positive role in the control of environmental desertification. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The figure is a schematic diagram of the appearance of the composite cat litter prepared in the example.

[0032] Figure 2 This is a schematic diagram of the composite cat litter prepared in Example after absorbing water and agglomerating.

[0033] Figure 3 It is a schematic diagram of the composite cat litter prepared in the examples and comparative examples after continuous agglomeration. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0035] The raw material information used in the examples and comparative examples is shown below.

[0036] Sodium bentonite 1, colloid price 351.7ml / 15g, No. 1 mine, Liufangzi, Jilin.

[0037] Sodium bentonite 2, colloid price 169.3ml / 15g, bentonite crushed sand, Henan Jiongbao.

[0038] Sodium bentonite 3, colloid value 605.1ml / 15g, AIT K, Weike.

[0039] Sodium bentonite 4, colloid value 715.6ml / 15g, AIT K3, Weike.

[0040] Calcium bentonite, colloid price 262ml / 15g, calcium bentonite powder, Tianyu.

[0041] Pregelatinized starch 1, gelatinization degree 81.3%, mass content of amylopectin 78.8%, cassava pregelatinized starch, Renqiu Yibang Environmental Protection Technology Co., Ltd.

[0042] Pregelatinized starch 2, gelatinization degree 85.3%, mass content of amylopectin 82.8%, potato pregelatinized starch, Hefei Pinshengyuan Food Ingredients Co., Ltd.

[0043] Pregelatinized starch 3, gelatinization degree 73.2%, mass content of amylopectin 82.8%, potato pregelatinized starch, Hefei Pinshengyuan Food Ingredients Co., Ltd.

[0044] Pregelatinized starch 4, gelatinization degree 63.7%, mass content of amylopectin 77.8%, corn pregelatinized starch, Renqiu Yibang Environmental Protection Technology Co., Ltd.

[0045] Pregelatinized starch 5, gelatinization degree 91.2%, mass content of amylopectin 77.8%, corn pregelatinized starch, Renqiu Yibang Environmental Protection Technology Co., Ltd.

[0046] Pregelatinized starch 6, gelatinization degree 78.8%, mass content of amylopectin 62.8%, rice pregelatinized starch, Dalian Shenghegu Agricultural Development Co., Ltd.

[0047] Pregelatinized starch 7, gelatinization degree 79.5%, mass content of amylopectin 95.4%, glutinous rice pregelatinized starch, Xinghua Lvshuai Food Co., Ltd.

[0048] Anionic polyacrylamide 1, molecular weight 18 million, Henan Saike Environmental Protection Technology Co., Ltd.

[0049] Anionic polyacrylamide 2, molecular weight 14 million, Henan Saike Environmental Protection Technology Co., Ltd.

[0050] Anionic polyacrylamide 3, molecular weight 20 million, Henan Saike Environmental Protection Technology Co., Ltd.

[0051] Anionic polyacrylamide 4, molecular weight 8 million, Henan Saike Environmental Protection Technology Co., Ltd.

[0052] Anionic polyacrylamide 5, molecular weight 26 million, Henan Saike Environmental Protection Technology Co., Ltd.

[0053] Desert sand 1, desert sand, particle size is 0.5-2.5mm, Lingshou County Huachen Mineral Products Trading Co., Ltd.

[0054] Desert sand 2, desert sand, particle size is 1-4mm, Lingshou County Shuntian Mineral Products Processing Plant.

[0055] Example 1

[0056] The weight parts of the raw materials used in Example 1 are shown in Table 1.

[0057] A composite cat litter comprises the following specific preparation steps: firstly, sodium bentonite, pregelatinized starch and polyacrylamide are uniformly mixed in a mixer, then, deionized water is dripped into a disc granulator while granulating to obtain spherical particles, then, the particles are dried at 220°C until the moisture content of the particles is below 8%, then, the particles are uniformly mixed with desert sand, and dust is removed by sieving to obtain the composite cat litter (such as Figure 1 shown).

[0058] Example 2-Example 11

[0059] The weight parts of the raw materials used in the following examples are shown in Table 1.

[0060] The specific preparation steps of the following examples are the same as those of Example 1.

[0061] Comparative Example 1-Comparative Example 7

[0062] The weight parts of the raw materials used in the following comparative examples are shown in Table 2.

[0063] The specific preparation steps of other comparative examples are the same as those of Example 1.

[0064] Table 1

[0065]

[0066]

[0067] Table 2 shows the formula components of each comparative example:

[0068] Table 2

[0069] Components Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Desert Sand 1 75 75 75 75 75 75 75 Sodium bentonite 1 19 19 19 19 19 19 / Calcium Bentonite / / / / / / 19 Pregelatinized starch 1 / / / / 2.8 2.8 2.8 Pregelatinized starch 4 2.8 / / / / / / Pregelatinized starch 5 / 2.8 / / / / / Pregelatinized starch 6 / / 2.8 / / / / Pregelatinized starch 7 / / / 2.8 / / / Polyacrylamide 1 2.5 2.5 2.5 2.5 / / 2.5 Polyacrylamide 4 / / / / 2.5 / / Polyacrylamide 5 / / / / / 2.5 / Deionized water 0.7 0.7 0.7 0.7 0.7 0.7 0.7

[0070] The test method of the composite cat litter prepared in the above embodiments and comparative examples is as follows.

[0071] (1) Clumping thickness: Weigh enough sample and spread it in a plastic container with a thickness of 4.5 cm. Use a syringe to inject 20 mL of warm water at 39°C into the sample, pour out the clumping sample, and use a vernier caliper to measure the vertical height from the water absorption surface to the lower end. The smaller the clumping thickness, the less likely it is to stick to the bottom under normal laying thickness. Figure 2 , which is a schematic diagram of the composite cat litter prepared in Example after absorbing water and agglomerating.

[0072] (2) Agglomeration weight: Weigh a sufficient amount of sample and spread it flat in a plastic container with a thickness of 4.5 cm. Use a syringe to inject 20 mL of warm water at 39°C into the sample, pour out the agglomerated sample, and weigh it with an electronic balance. The smaller the agglomeration weight, the less loss during use and the more durable the cat litter. On the other hand, the smaller the agglomeration weight, the smaller the volume of the cat litter, so the risk of sticking to the bottom or wall will be smaller.

[0073] (3) Agglomeration strength: Weigh a sufficient amount of sample and spread it flat in a plastic container with a thickness of 4.5 cm. Use a syringe to inject 20 mL of warm water at 39°C into the sample, pour out the agglomerated sample and weigh it as m. Use a cat litter shovel to throw the agglomerate 5 times (the height is not less than 25 cm), and then weigh it as M. The agglomeration strength = (M / m) × 100%. The greater the agglomeration strength, the stronger the cat litter is, and the agglomerate is less likely to fall apart when stepped on by a cat or touched by a shovel. Figure 3 Shown is a schematic diagram of the composite cat litter prepared in the embodiments and comparative examples after continuous agglomeration.

[0074] (4) Water absorption rate: Weigh a sufficient amount of sample and spread it flat in a plastic container with a thickness of 4.5 cm. Use a syringe to inject 20 mL of warm water at 39°C into the sample. Record the time required for the water on the surface of the cat litter to be completely absorbed from the beginning of the dripping. Measure three times and take the average value.

[0075] The specific test results are shown in Table 3 and Table 4.

[0076] Table 3

[0077]

[0078] Table 4

[0079] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Thickness of cluster / cm 4.3 3.6 4.7 4.8 4.5 4.6 4.0 Agglomeration weight / g 75.0 76.7 82.2 79.1 83.8 72.1 86 Agglomeration strength / % 76.1 92.0 78.0 91.2 87.9 91.5 82.7 Water absorption speed / s 2 5 2 5 2 6 3

[0080] As can be seen from Tables 3 and 4 above, the agglomeration composition provided by the present invention has good agglomeration strength, is less likely to stick to the bottom, and has excellent water absorption speed, and can form agglomerates quickly. More specifically, when the agglomeration composition provided by the present invention is used as a composite cat litter, its agglomeration thickness is ≤4.0cm; agglomeration weight is ≤80g; agglomeration strength is ≥85%; and water absorption speed is ≤4s. Further preferably, the agglomeration thickness is ≤3.2cm; agglomeration weight is ≤73.8g; agglomeration strength is ≥92.4%; and water absorption speed is ≤2s.

[0081] It can be seen from Examples 1 to 4 that when the colloidal value of sodium bentonite is within a specific range, the agglomerate composition has a smaller agglomerate thickness and agglomerate weight, is less likely to stick to the bottom, and has less loss; it has better agglomerate strength and water absorption speed.

[0082] It can be seen from Example 1 and Comparative Examples 1 to 4 that when the degree of gelatinization of pregelatinized starch and the mass content of amylopectin are within a specific range, the agglomeration composition has better agglomeration strength, is less likely to stick to the bottom, and has less loss; and has better agglomeration strength and water absorption speed, and can quickly agglomerate.

[0083] It can be seen from Example 1, Comparative Example 5 and Comparative Example 6 that when the molecular weight of polyacrylamide is within a specific range, it is difficult to achieve the technical effect of the present invention.

[0084] It can be seen from Example 1 and Comparative Example 7 that when calcium-based bentonite is used, the agglomeration weight and agglomeration strength of the agglomeration composition after contacting water are difficult to achieve the technical effects of the present invention, and its water absorption rate and agglomeration thickness are also significantly reduced.

[0085] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges therein, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.

Claims

1. A clumping composition, characterized in that According to weight parts, it includes: 74-76 parts of desert sand, 18-22 parts of sodium bentonite, 2-3 parts of pregelatinized starch, 1-3 parts of polyacrylamide, and 0.5-1.5 parts of solvent; The gelatinization degree of the pregelatinized starch is 73-86%, and the mass content of amylopectin in the pregelatinized starch is 75-84%; The molecular weight of the polyacrylamide is 14 million to 20 million.

2. The agglomeration composition according to claim 1, characterized in that In the sodium bentonite, the colloid value is 350-620ml / 15g.

3. The agglomeration composition according to claim 1, characterized in that The solvent is selected from water, or a mixed solution of an alcohol solvent and water.

4. The agglomeration composition according to claim 1, characterized in that: Calculated by weight, the composition comprises: 74-76 parts of desert sand, 18-20 parts of sodium bentonite, 2.5-2.8 parts of pregelatinized starch, 2-2.8 parts of polyacrylamide and 0.5-0.8 parts of solvent.

5. The agglomerating composition according to claim 1, characterized in that: The gelatinization degree of the pregelatinized starch is 73.2-85.3%, and the mass content of amylopectin in the pregelatinized starch is 78.8-82.8%.

6. The agglomerating composition according to claim 1, characterized in that: The agglomerated composition has a diameter of 0.5-4 mm.

7. The agglomerating composition according to claim 1, characterized in that: The moisture content of the agglomeration composition is ≤ 8%.

8. The method for preparing the agglomeration composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing sodium bentonite, pregelatinized starch, polyacrylamide and a solvent, granulating, drying, and then mixing with desert sand to prepare the agglomeration composition.

9. Use of the agglomerating composition according to any one of claims 1 to 7 in the preparation of cat litter.

10. A composite cat litter, characterized in that: Contains the agglomeration composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Cat litter with sand grains

    CN116508660A

  • Cat litter and preparation method thereof

    CN117502252A

  • Clumping animal litter and method thereof

    US20240156046A1

Cited By

  • Cassava cat litter and preparation and production method thereof

    CN120615743A